Idealism, materialism, and Vygotsky’s cultural historical theory - von Schulz, Gustav A. (Frontiers in Psychology, 2024)
Vygotsky straddled the period of the Russian Revolution and found himself facing the Marxist materialist ideology of the Soviet Union and the need for a new method of psychology. Ironically, the Soviet Union's need for a Marxist based method of psychology coincided with Vygotsky's prior research on methods of interpretation which were inspired by Hegel and primarily based on the role of consciousness and culture. As a result of Vygotsky's prerevolutionary work and inspiration from Hegel clashing with the post-revolutionary need for a new methodology for psychology, Vygotsky developed his Cultural Historical Theory. In presenting his new theory, Vygotsky attempted to resolve a fundamental ideological conflict between idealism and materialism. Furthermore, Vygotsky worked to create an effective new research method by drawing inspiration from Gestalt psychology, Hegel, Marx, and Engels. The result of Vygotsky's efforts was a theory based on psychology of consciousness and mind rather than a biology-based psychology focused entirely on analysis of stimuli and responses. In analyzing Vygotsky's theory, it is useful to draw inspiration from Vygotsky's criticism of pure empiricism, and to be inspired by Vygotsky's demonstration on how deeply rooted differences between societies may be bridged by finding unexpected commonalities within opposing ideologies.